ChemInform Abstract: On the Understanding of BF3·Et2O‐Promoted Intra‐ and Intermolecular Amination and Oxygenation of Unfunctionalized Olefins. Issue 47 (November 2015) - Yang, Chun‐Hua; Fan, Wen‐Wen; Liu, Gong‐Qing; Duan, Lili; Li, Lin; Li, Yue‐Ming
Abstract: BF3 .Et2 O is effective for both intra‐ and intermolecular hydroamination as well as for lactonization and esterification reactions of unactivated C=C double bonds.